Analysis of knowledge regarding Biliary Atresia among healthcare providers and laypersons in East Jakarta after educational intervention - Lianti, Hanna; Kurnia, Novi; Rinaldhy, Kshetra; Aji, Amanda Safira; Ismet, M Febriadi; Amaliah, Rizky (UI Scholars Hub, 2020)
Biliary atresia (BA) is the most common cause of death due to liver disease in children and is the most common indication for pediatric liver transplantation. The success rate of the management of BA is very dependent on the age of the patient at the time of surgery. However, patients with BA were often diagnosed late because of the lack of parents’ and primary healthcare providers’ knowledge regarding BA. This study aims to evaluate the effectiveness of health education in improving the knowledge of healthcare providers and laypersons. A total of 371 respondents participated in this pre-post study with no control group, consisting of 234 laypersons (community health workers, new mothers, and expectant mothers) and 137 healthcare providers (medical doctors, midwives, and nurses). There were significant increases in the median values between pretest and posttest knowledge scores in both the healthcare provider and layperson groups (p < .05). Health education was effective in increasing public knowledge about BA.